Cultural Influences on Entrepreneurial Orientation: The Impact of National Culture on Risk Taking and Proactiveness in SMEs - Kreiser, Patrick M.; Marino, Louis D.; Dickson, Pat; Weaver, K. Mark (Entrepreneurship Theory and Practice, 2010)
This study utilizes data from 1,048 firms in six countries to assess the impact of national culture and certain institutions that are representative of national culture on two key dimensions of entrepreneurial orientation: risk taking and proactiveness. Eight hypotheses are developed specifying the expected relationships between four cultural dimensions and levels of risk taking and proactiveness within SMEs. Additionally, two hypotheses are developed to explore between–country differences in the relationship between risk taking and proactiveness and a range of institutional variables. Uncertainty avoidance and power distance are both found to have a significant negative influence on risk taking; uncertainty avoidance, individualism, and power distance are found to negatively influence proactive firm behaviors. A number of institutional factors are also found to be significantly linked to between–country differences in both risk taking and proactive behaviors. This research contributes to existing theories of national culture by suggesting that the various dimensions of cultural values and several of the institutions that are representative of national culture impact the willingness of entrepreneurial firms to display risk taking and proactive behaviors.